Crypto Currency Investment from an Islamic Law Perspective: An Overview of Guidelines and Considerations - Hafiz, Abdul; Napisah Napisah; Ismail Jalili; Armasito Armasito; Abdul Kabir Hussain Solihu (Nurani: jurnal kajian syari’ah dan masyarakat, 2025)
This study seeks to offer an in-depth examination of cryptocurrency investments through the lens of Islamic law, with particular emphasis on assessing the Shariah compatibility of widely used digital assets such as Bitcoin and Ethereum. The novelty of this research lies in its systematic exploration of key issues such as the speculative nature, intrinsic value, and potential for financial harm (gharar) associated with cryptocurrencies. This study adopts a qualitative approach, drawing upon primary sources of Islamic jurisprudence namely the Quran, Hadith, and classical scholarly interpretations while also incorporating contemporary fatwas, insights from prominent Islamic finance scholars, and expert interviews to inform the analysis. The results highlight divergent viewpoints on the permissibility of cryptocurrency investments, with some scholars asserting their compliance under specific conditions, while others deem them non-compliant due to risks of speculation and uncertainty. The study concludes by proposing a set of actionable guidelines for Muslim investors, underscoring the significance of grasping the intricacies of Shariah principles in cryptocurrency investments and highlighting the necessity for continuous scholarly engagement in this evolving domain.